Hyper Expression of Mucin 5ac Indicates Poor Cancer Prognoses: A Meta-Analysis. Issue 1 (January 2016) - Wang, Xin; Yan, Fei; Shi, Run; Huang, Xing; Lu, Shiming; Xu, Lin; Ren, Binhui
Abstract : Abstract: The aim of the study was to explore the association between mucin 5ac expression and cancer prognosis. A systematically comprehensive search was performed through PubMed, the Web of Science, and the China National Knowledge Infrastructure (CNKI). The prognostic value of mucin 5ac expression in cancer patients was evaluated. The overexpression of mucin 5ac was found to be significantly associated with a poor prognosis in cancer patients (pooled HR: 1.53, 95%CI: 1.158–2.028, P  = 0.003). This association was also detected in a biliary subgroup (pooled HR: 1.83, 95%CI: 1.269–2.639, P  = 0.001) and a gastrointestinal subgroup (pooled HR: 1.44, 95%CI: 1.069–1.949 P  = 0.017). In the geography subgroup analysis, a statistical association was found in the Asian subgroup (pooled HR: 1.69, 95%CI: 1.200–2.384, P  = 0.003). In the clinical characteristics analysis, a statistical association was found between the hyper expression of mucin 5ac and lymphatic metastasis. We indicated that mucin 5ac is a promising prognostic predictor for cancer, especially for biliary and gastrointestinal cancer, and is more suitable for predicting cancer prognoses in Asians.